Pembuatan Video Profil Sekolah Menengah Pertama Negeri 1 Mojogedang Karanganyar - Wulandari, Siwi Eka Titi; Nugrohotomo, Gesang Kristianto (Seruni - Seminar Riset Unggulan Nasional Inoformatika dan Komputer, 2013)
ABSTARCTS : Along with the development of information technology and the tremendous work that in practice researchers will create a video profile titled